Pelatihan Living Hadits Bagi Santri Pondok Pesantren Darussalam Parmeraan Kecamatan Sipongot Kabupaten Padang Lawas Utara Sumatera Utara - Siregar, Ilham Ramadan; Ritonga, Raja; Hamid, Asrul; Akhyar, Akhyar; Amiruddin, Amiruddin; Nst, Andri Muda; Ritonga, Syaipuddin; Hasibuan, Sri Wahyuni (Journal of Humanity Dedication, 2024)
Living Hadith is a concept in Islam that has an important role as a source of inspiration in everyday life. This concept refers to Islamic teachings that are alive and relevant to the context of society. The application of Living Hadith can help students to overcome daily life problems and provide guidance in behavior. Therefore, a better understanding of the concept of Living Hadith needs to be improved among students. This training aims to help participants instill students' understanding of living hadith studies. This training activity was carried out at the Darussalam Parmeraan Islamic boarding school located in Parmeraan Village, Sipiongot District, North Padang Lawas Regency, North Sumatera. The research method used is to conduct a pre-test at the beginning of the training, followed by presentation activities, and discussions on understanding living hadith. Then continued with questions and answers continued with evaluation through post-test activities. The results of the service show that students of the Darussalam Parmeraan Islamic boarding school need to understand that Living Hadith is a relevant Islamic teaching to be applied in the context of modern society. A better understanding of Living Hadith can help students in solving daily life problems and provide guidance in behaving in accordance with Islamic teachings.